Dissolution behavior of core structure materials by molten corium in boiling water reactor plants during severe accidents. Issue 3 (4th March 2018) - Sumita, Takehiro; Urata, Kentaro; Morita, Yuya; Kobayashi, Yoshinao
ABSTRACT: For the decommissioning of the Fukushima Daiichi Nuclear Power Plant, it is necessary to consider the access route to the fuel debris for its removal, which can be determined by knowing the corruption situation of the core support structure. To predict the damage condition of reactor vessel, dissolution behavior of the core structure material should be understood. In this study, the dissolution behavior of core structure materials (stainless steel) by molten metallic corium (stainless steel + B4 C) originated from control rod and its cladding was investigated. As a result of immersion experiment, it was found that there were two types of dissolution mode in this system: (1) chemical dissolution by eutectic reaction between Fe and B and (2) physical dissolution caused by the grains falling off from solid steel due to infiltration of molten metal. Moreover, on the basis of kinetic analysis, it was considered that the chemical dissolution in this system was slow. Therefore, the dissolution is considered to mainly occur through the mechanism that physical dissolution precedes chemical dissolution.